Retirement home smoking cessation - NEVES, João Emmanuel D'Alkmin; SILVA, Antonio André Cunha da (004, 2015)
This paper analyzes the opinion of health staff members about retirement home residents on tobacco cessation through a data mining approach. This analysis mainly aims the identification of which type of professional is more willing to give advice to people who live in retirement home. In this manner, a bunch of questions were answered by the health staff and converted into a amount of variables. These variables were preprocessed and cleaned and used as entry to sophisticated methods using the Data Mining Program called Waikato Environment for Knowledge Analysis (WEKA). Those methods were classification, association, and clustering. As a result, we had the most willing profession.
Keywords: Mineração de dados; Tabagismo; Informação e Comunicação